(untitled) (Colombia Medica, 2009)
Objective: To establish the periodontal status in female psychiatric patients from «Nuestra Señora del Perpetuo Socorro» Mental Hospital at Pasto, Colombia in 2007. Methodology: We evaluated 59 patients and assessed Quigley-Hein and sulcus bleeding indexes, clinical attachment loss, probing depth, gingival enlargement, tooth displacement, and furcation involvement. Variables such as age, hospitalization, mental illness, other systemic condition and psychiatric medications were analyzed. Results: The Quigley-Hein Index was 3.05, SD=1.56, sulcus bleeding index on probing index was 3.08, SD=1.54. Of the women 49.2% had a clinical attachment loss (CAL) of 7 mm. There was an increasing percentage of CAL from 5 to 7 mm in patients with more than 10 years of hospitalization. Women with schizophrenia and mental retardation showed CAL from 2 to 7 mm. Patients who ingested antipsychotics-antiparkinsonians had CAL of 17 mm. Conclusions: Periodontal disease is severe in these patients and might be influenced by hospitalization, mental illness, and medication.